Low-dose photodynamic therapy promotes a cytotoxic immunological response in a murine model of pleural mesothelioma. (5th May 2020) - Cavin, Sabrina; Gkasti, Aspasia; Faget, Julien; Hao, Yameng; Letovanec, Igor; Reichenbach, Maxime; Gonzalez, Michel; Krueger, Thorsten; Dyson, Paul J; Meylan, Etienne; Perentes, Jean Y
Abstract: OBJECTIVES: Malignant pleural mesothelioma (MPM) is a deadly disease with limited treatment options. Approaches to enhance patient immunity against MPM have been tested but shown variable results. Previously, we have demonstrated interesting vascular modulating properties of low-dose photodynamic therapy (L-PDT) on MPM. Here, we hypothesized that L-PDT vascular modulation could favour immune cell extravasation in MPM and improve tumour control in combination with immune checkpoint inhibitors. METHODS: First, we assessed the impact of L-PDT on vascular endothelial E-selectin expression, a key molecule for immune cell extravasation, in vitro and in a syngeneic murine model of MPM. Second, we characterized the tumour immune cell infiltrate by 15-colour flow cytometry analysis 2 and 7 days after L-PDT treatment of the murine MPM model. Third, we determined how L-PDT combined with immune checkpoint inhibitor anti-CTLA4 affected tumour growth in a murine MPM model. RESULTS: L-PDT significantly enhanced E-selectin expression by endothelial cells in vitro and in vivo . This correlated with increased CD8 + T cells and activated antigen-presenting cells (CD11b + dendritic cells and macrophages) infiltration in MPM. Also, compared to anti-CTLA4 that only affects tumour growth, the combination of L-PDT with anti-CTLA4 caused complete MPM regression in 37.5% of animals. CONCLUSIONS: L-PDT enhances E-selectin expression in the MPM endothelium, which favours immune infiltration of tumours. The combination of L-PDT with immune checkpoint inhibitor anti-CTLA4 allows best tumour control and regression.